Kesalahan fonologi mahasiswa Vietnam tingkat BIPA 1 dalam pelafalan fonem bahasa Indonesia - Andriyana Andriyana; Huynh hoang van anh; Daroe Iswatiningsih (Badan Pengembangan dan Pembinaan Bahasa, 2022)
Different languages have different phonetic systems, this is the distinguishing feature of a foreign learner in learning a second language. This paper describes the phonological errors of Vietnamese students after surveying Indonesian by recording pronunciation based on the distribution of phonemes to several students from The Open University. The data was then reduced based on the consistency of students' pronunciation errors in the three participants. Every word that was successfully pronounced correctly by the three participants was considered to have been represented and was able to be pronounced by Vietnamese students. Data reduction is based on the possibility of errors that occur continuously in Indonesian foreign speakers. The results showed that students had pronunciation errors, especially the phonemes /sy/ and /r/. Based on the Vietnamese phonetic system, the author observes that students can improve their Indonesian language skills through practice with several applications on the Internet, for example, the writing application of phonetics.glideapp.io